Limbal Stem Cell Transplantation: Clinical Results, Limits, and Perspectives - Marta Sacchetti; Paolo Rama; Alice Bruscolini; Alessandro Lambiase (Stem Cells International)
Limbal stem cell deficiency (LSCD) is a clinical condition characterized by damage of cornea limbal stem cells, which results in an impairment of corneal epithelium turnover and in an invasion of the cornea by the conjunctival epithelium. In these patients, the conjunctivalization of the cornea is associated with visual impairment and cornea transplantation has poor prognosis for recurrence of the conjunctivalization. Current treatments of LSCD are aimed at replacing the damaged corneal stem cells in order to restore a healthy corneal epithelium. The autotransplantation of limbal tissue from the healthy, fellow eye is effective in unilateral LSCD but leads to depauperation of the stem cell reservoir. In the last decades, novel techniques such as cultivated limbal epithelial transplantation (CLET) have been proposed in order to reduce the damage of the healthy fellow eye. Clinical and experimental evidence showed that CLET is effective in inducing long-term regeneration of a healthy corneal epithelium in patients with LSCD with a success rate of 70%–80%. Current limitations for the treatment of LSCD are represented by the lack of a marker able to unequivocally identify limbal stem cells and the treatment of total, bilateral LSCD which requires other sources of stem cells for ocular surface reconstruction.